Reviewing Ideological State Apparatus and Repressive State Apparatus in the Snowpiercer by Bong Joon Ho - Sharma, Naresh Regmi (Journal of Rapti Babai Campus, 2026)
This study explores the existence of the state as a repressive and ideological apparatus even in the futuristic world in Bong Joon Ho’s Snowpiercer. To analyze this, Marxist theory of the state and Louis Althusser’s concepts of the Ideological State Apparatus (ISA) and the Repressive State Apparatus (RSA) have been used. It aims to focus on the character of the state in a system that is divided into classes. The paper uses a qualitative, interpretive, and text-based film study as its methodology. There are mainly three key findings in this research paper. First, the state is always repressive by its character indifferent to time and situation. Second, ideology is the main base of the state no matter in what situation it operates. Finally, the working class must revolt and occupy the means of production to have a state that works in their favor. Even the devastation of the world and the only remaining closed ecosystem could not change this character. Therefore, revolt becomes compulsory at a certain point. This paper concludes that the repressive and ideological character of the state persists in any kind of situation. It has mainly six sections which are introduction, literature review, statement of the problem, research objective, methodology, and conclusion.